Access to justice for disadvantaged communities - Mayo, Marjorie 1943-; Kössl, Gerald ca. 20./21. Jh; Slater, Imogen ca. 20./21. Jh; Scott, Matthew ca. 20./21. Jh (Policy Press, 2014)
This unique study explores how strategies to safeguard the provision of legal advice and access to welfare rights to disadvantaged communities might be developed in ways that strengthen rather than undermine the basic ethics and principles of public service provision